Digitization Transformation Empowers High-Quality Development of Small and Medium-Sized Enterprises in Jilin Province - Wang, Yan (Transactions on Economics, Business and Management Research, 2024)
In the rapidly evolving digital landscape, small and medium-sized enterprises (SMEs) in Jilin Province, China, face a critical juncture in their growth and sustainability. This paper delves into the current state of digital transformation among these SMEs, examining the intricate web of opportunities and challenges that define their journey towards a digital future. Through a comprehensive analysis, we explore the various facets of digital transformation, including the provincial government's support initiatives, the strategic approaches adopted by SMEs, and the inherent hurdles such as increased operational costs, leadership and cultural challenges, skill gaps, and technological adoption issues. The findings underscore the importance of a multi-pronged strategy involving government support, private sector collaboration, workforce development, and fostering a culture of innovation and adaptability. The paper highlights the need for Jilin's SMEs to not only embrace technological changes but also to rethink their operational models to stay competitive in a global digital economy. Looking ahead, the paper suggests that with continuous strategic efforts, policy support, and an adaptive mindset, SMEs in Jilin can successfully navigate their digital transformation journey, tapping into new opportunities for growth and innovation in an increasingly digital world. The future trajectory for these enterprises is one of continued evolution, where adaptability and strategic planning are key to harnessing the full potential of digital technologies. As digital transformation continues to reshape the global business landscape, SMEs in Jilin Province stand on the brink of significant opportunities, poised to redefine their role in the regional and global economy through innovative and sustainable digital strategies.